S94 The relationship between CT-derived measurements of thoracic muscle and fat with disease severity in COPD. (December 2018) - Wilcox, CR; Ostridge, K; Misra, B; Wojtas, M; Wootton, S; Staples, K; Devaster, JM; Wilkinson, TMA
Abstract : Introduction: COPD is a heterogeneous disease with multiple extra-pulmonary manifestations, including cachexia and skeletal muscle wasting. These co-morbidities relate to early mortality but are poorly characterised by measures including weight and BMI. Much of the CT-based body composition literature has focussed on abdominal scans. Using conventional chest CT, we aimed to assess the use of CT-derived measures of thoracic muscle and fat in COPD and report their relationship with traditional measures of body composition and markers of disease severity. Methods: AERIS was a two-year study involving patients aged 40–85 with moderate-to-very-severe COPD. At enrollment subjects had pulmonary-function-testing, body composition measurements (BMI and bioelectrical impedance at 50 Hz [R50])and chest CT. 3D-Slicer software was used for semi-automated measurements of cross-sectional areas (CSA) of thoracic muscle (pectoralis [PM], erector spinae [ESM] and chest-wall [CWM]) and fat (TF) on the CT scans, with pre-defined attenuation values used to detect muscle (−29 to +150 HU) and fat (−190 to −30HU) boundaries. PM/TF and ESM were identified on an axial slice at the level of the aortic arch and the 12th thoracic vertebra, respectively. CWM were identified on a coronal slice at the point at which the inferior margin of the trachea was level with the lung apices. Results: 120 subjects had CT-derived body composition data. PM was significantly correlated (p<0.05) with ESM (r=0.49), CWM (r=0.53) and TF (r=0.24). BMI had significant associations with PM (r=0.24), ESM (r=0.34), CWM (r=0.21) and TF (r=0.73), and bioelectrical impedance significantly correlated with PM (r=−0.55), ESM (r=−0.50) and CWM (r=−0.49), but not with TF. GOLD groups 2, 3 and 4 displayed significant variance in median CSA of pectoralis muscle (1459.8, 1230.9 and 1228.3 mm 2, p<0.033), thoracic fat (2396.1, 2443.3 and 1550.6 mm 2, p<0.049) and BMI (27.7, 26.6 and 25.4kg/m 2, p<0.023). On multiple regression (table 1), PM, TF and BMI were associated with FEV1% and emphysema, and PM and BMI were associated with six-minute-walk-distance. Conclusions: CT-derived measurements of pectoralis muscle and thoracic fat showed significant associations with traditional measures of body composition and markers of disease severity. Further studies are therefore warranted to establish the value of these markers in clinical decision making.